Injection molded product

A bimodal molecular weight distributed polyethylene composition using a co-supported metallocene catalyst system addresses the challenges of moldability and mechanical properties in ultra-high molecular weight polyethylene, resulting in improved injection moldability and mechanical strength for thinner, longer-lasting products.

JP2025011668APending Publication Date: 2025-01-24TOSOH CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023113903
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing polyethylene compositions, particularly ultra-high molecular weight polyethylene, face challenges in achieving excellent impact resistance, mechanical properties, and abrasion resistance while maintaining good injection moldability and processability.

Method used

A polyethylene composition with a bimodal molecular weight distribution, comprising ethylene resin and polyethylene with specific melting characteristics, is formulated using a co-supported metallocene catalyst system, ensuring a balanced melt flow rate and molecular weight distribution for improved injection moldability and mechanical properties.

Benefits of technology

The composition achieves enhanced injection moldability, impact resistance, and mechanical strength, allowing for thinner wall thickness and extended product life, suitable for various applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011668000001
    Figure 2025011668000001
  • Figure 2025011668000002
    Figure 2025011668000002
  • Figure 2025011668000003
    Figure 2025011668000003
Patent Text Reader

Abstract

To provide an injection molded product composed of a polyethylene composition comprising polyethylene and a high-molecular-weight ethylene-based resin with a bimodal molecular weight distribution, the injection molded product featuring superior impact resistance, mechanical characteristics and wear resistance.SOLUTION: An injection molded product is composed of a polyethylene composition comprising: an ethylene-based resin having a HLMFR of 0.01-100 g / 10 min at 190°C under a 21.6 kg load, with a bimodal elution curve as measured by GPC; and a polyethylene with a MFR of 0.1-100 g / 10 min at 190°C under a 2.16 kg load and a density of 930 to 980 kg / m3.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a specific injection molded article, and more specifically, to an injection molded article that is excellent in injection moldability, impact resistance, mechanical properties, and abrasion resistance, and is expected to have a thinner wall and a longer life as a molded article. [Background technology]

[0002] Polyethylene is a resin used in a wide range of applications, and in order to make it suitable for each application, technologies have been proposed to control the molecular weight distribution and composition by combining two or more resin components, thereby improving various physical properties and appearance. For example, an increase in higher molecular weight components improves mechanical strength but decreases moldability, while an increase in lower molecular weight components decreases mechanical strength but improves moldability.

[0003] As a method for combining two or more types of polyethylene components, there have been proposed a method in which each component is polymerized and then blended by melt kneading or dry blending, a method in which multi-stage polymerization is carried out continuously, a method in which two or more types of polyethylene components are simultaneously produced by adding a plurality of transition metal catalysts to a polymerization system, a method in which a combination of these is carried out, etc. In addition, a resin modifier has also been proposed (see, for example, Patent Document 1) that is blended with a target material to modify the physical properties, appearance, etc. of the target material.

[0004] In the drawing, spinning, blow molding, injection molding, inflation molding, and extrusion molding of polyethylene, materials with good moldability and physical properties are generally required. In recent years, there has been a demand for lighter weight and thinner walls to reduce costs, but at the same time, there is a demand for excellent mechanical strength.

[0005] Ultra-high molecular weight polyethylene, which has attracted attention in recent years (see, for example, Patent Documents 2 and 3), has an extremely high molecular weight equivalent to a viscosity average molecular weight (hereinafter sometimes referred to as Mv) of 1 million or more, and therefore has excellent impact resistance, self-lubrication, abrasion resistance, weather resistance, chemical resistance, dimensional stability, etc., and has high physical properties comparable to those of engineering plastics. For this reason, attempts have been made to apply it to uses such as sheets, films, high-strength fibers, sliding members, lining materials, line parts in the food industry, machine parts, artificial joints, sporting goods, microporous membranes, and separators by various molding methods.

[0006] However, because of its high molecular weight, ultra-high molecular weight polyethylene has extremely low fluidity when melted, and it is difficult to mold it by kneading and extrusion like ordinary polyethylene, which has a molecular weight in the range of several tens of thousands to about 300,000.Therefore, ultra-high molecular weight polyethylene is molded by various methods, such as direct sintering of the polymer powder obtained by polymerization, compression molding, molding using a ram extruder in which extrusion molding is performed while intermittently compressing, and extrusion molding into a sheet, film, or fiber shape in a state where it is uniformly mixed with a plasticizer, and in some cases, stretching it and then removing the solvent.

[0007] In order to improve the moldability of ultra-high molecular weight polyethylene and its mixability with other resins, a method of adding low molecular weight polyethylene has been proposed (see, for example, Patent Documents 4 and 5), and an ultra-high molecular weight polyethylene exhibiting a specific melting behavior has been proposed (see, for example, Patent Document 6). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2017-179304 A [Patent Document 2] Patent No. 4868853 [Patent Document 3] Patent No. 6405888 [Patent Document 4] Patent No. 4173444 [Patent Document 5] Patent No. 7071966 [Patent Document 6] JP 2021-172716 A Summary of the Invention [Problem to be solved by the invention]

[0009] However, although the modified material proposed in Patent Document 1 was effective in improving processability to a certain extent, further improvement was required in terms of improving mechanical strength.

[0010] Moreover, Patent Documents 2 and 3 merely propose ultra-high molecular weight polyethylene, and have problems with moldability. The proposals in Patent Documents 4 to 6 also only improve the processability of ultra-high molecular weight polyethylene, and still have problems with versatility.

[0011] Therefore, there has been a demand for the development of injection molded articles that are excellent in impact resistance, mechanical properties and abrasion resistance without impairing the processability, particularly injection moldability, of general-purpose resins. [Means for solving the problem]

[0012] Means for Solving the Problems The present inventors have conducted intensive studies to solve the above problems and have found that a polyethylene composition of an ethylene-based resin and a polyethylene having specific melting properties and molecular weight configuration has excellent injection moldability and can give an injection molded article having excellent impact resistance, mechanical properties and abrasion resistance, thereby completing the present invention.

[0013] That is, the present invention relates to: (1) an ethylene-based resin having a high melt flow rate (HLMFR) of 0.01 to 100 g / 10 min at a temperature of 190° C. and a load of 21.6 kg in accordance with JIS K6922-2:1997 and a bimodal elution curve measured by gel permeation chromatography; and (2) an ethylene-based resin having a melt flow rate (MFR) of 0.1 to 10 g / 10 min at a temperature of 190° C. and a load of 2.16 kg in accordance with JIS K6922-2:1997 and a density of 930 to 980 kg / m as measured according to JIS K6922-1 (1997). 3 The present invention relates to an injection-molded article characterized by being made of a polyethylene composition containing a polyethylene of the formula:

[0014] The present invention will be described in detail below.

[0015] The injection molded article of the present invention comprises: (1) an ethylene-based resin (C) having a melt flow rate (hereinafter sometimes referred to as HLMFR) of 0.01 to 100 g / 10 min at a temperature of 190° C. under a load of 21.6 kg in accordance with JIS K6922-2:1997 and a bimodal elution curve measured by gel permeation chromatography (hereinafter sometimes referred to as GPC); and (2) an ethylene-based resin (C) having a melt flow rate (hereinafter sometimes referred to as MFR) of 0.1 to 10 g / 10 min at a temperature of 190° C. under a load of 2.16 kg in accordance with JIS K6922-2:1997 and a density of 930 to 980 kg / m as measured according to JIS K6922-1 (1997). 3The polyethylene composition (e) containing polyethylene (d) is an injection molded article, and the ethylene resin (c) may be a bimodal ethylene resin having a relatively high molecular weight that exhibits melting behavior and a bimodal elution curve measured by GPC that exhibits two peaks, and examples of the ethylene homopolymer and ethylene-α-olefin copolymer are available. In this case, the α-olefin is, for example, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, etc., and ethylene homopolymer is preferable because it provides an injection molded article having excellent mechanical properties and abrasion resistance. Similarly, the polyethylene (d) may be, for example, ethylene homopolymer and ethylene-α-olefin copolymer, and in this case, the α-olefin is, for example, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, etc., and ethylene homopolymer is preferable because it provides an injection molded article having excellent mechanical properties and abrasion resistance.

[0016] The ethylene-based resin (iii) has (1) an HLMFR of 0.01 to 100 g / 10 min and exhibits melt fluidity. If the HLMFR is less than 0.01 g / 10 min, the melt fluidity is poor and the processability when forming an injection molded article is poor. On the other hand, if the HLMFR is more than 100 g / 10 min, the injection molded article will have poor mechanical properties.

[0017] The ethylene resin (iii) constituting the injection molded article of the present invention is an ethylene polymer having a bimodal molecular weight distribution, and preferably contains a specific ultra-high molecular weight polyethylene component (i) as a specific component, since it results in an injection molded article with excellent balance between processability and mechanical properties. In this case, the bimodal molecular weight distribution is preferably one in which the elution curve measured by GPC has two peaks, and when the elution curve is expressed as a differential molecular weight distribution (x-axis: Log [M], y-axis: differential distribution value) and the peaks are divided into two normal distributions (normal distribution of ultra-high molecular weight polyethylene component (i) and normal distribution of polyethylene component (ii)) according to the following formula (i), it satisfies (2-1) to (2-3). f(x)=a×(1 / (2π(σ 2 ))(1 / 2) ) exp(-((x-μ) 2 ) / (2(σ 2 ))) Formula (i) (Here, a is the peak intensity, σ is the standard deviation, x is the variable, and μ is the mean.) (2-1) The ultra-high molecular weight polyethylene component (a) (hereinafter may be referred to as component (a)) represented as a high molecular weight peak component has a weight average molecular weight (hereinafter may be referred to as Mw) of 900,000 to 5,000,000 and a molecular weight distribution expressed as Mw / number average molecular weight (hereinafter may be referred to as Mn) of 2.0 to 5.0, (2-2) The polyethylene component (b) (hereinafter may be referred to as component (b)) represented as a low molecular weight peak component has an Mw of 10,000 to 500,000 and an Mw / Mn of 2.0 to 5.0, and (2-3) the component (a) / component (b) (weight ratio) is greater than 5 / 95 and less than 80 / 20, and it is particularly preferable that the component (a) / component (b) (weight ratio) is 10 / 90 to 50 / 50.

[0018] When the ethylene-based resin (iii) is one in which the ultra-high molecular weight component (i) and the low molecular weight component (ii) coexist in a specific ratio, when blended with polyethylene, the component (i) can be highly dispersed, making it possible to highly modify the mechanical properties of the injection-molded article without impairing the appearance.

[0019] In order to obtain an injection-molded article having a particularly excellent balance between dispersibility in polyethylene and improved mechanical properties, the ethylene-based resin (C) preferably has (3) Mw / Mn, calculated as linear polyethylene as measured by GPC, of ​​4.0 or more and less than 50, and particularly preferably 4.0 or more and 30 or less.

[0020] In addition, since the components (A) and (B) are different from a simple blend in which each component is independently dispersed, the ethylene-based resin (C) is (4) measured using a differential scanning calorimeter (hereinafter sometimes referred to as DSC) by heating from 0°C to 230°C at a heating rate of 10°C / min (hereinafter sometimes referred to as 1st scan) at a crystal melting peak (hereinafter referred to as Tm 1 It is preferable that the peak intensity distribution is unimodal.

[0021] The ethylene-based resin (C) constituting the injection-molded article of the present invention may be any resin as long as it satisfies the above-mentioned characteristics. In particular, it is preferable that the resin is produced using a metallocene catalyst, since it is easy to control the molecular weight and molecular weight distribution and to produce an (ultra)high molecular weight resin. In particular, examples of a method for producing the ethylene-based resin (C) having both components (A) and (B) include a method using a co-supported catalyst in which two or more types of metallocene complexes are supported on a carrier as the catalyst system, and a method using multi-stage polymerization of two or more stages.

[0022] The polymerization method of the ethylene-based resin (iii) may be, for example, a solution polymerization method, a bulk polymerization method, a gas phase polymerization method, a slurry polymerization method, etc., among which, the slurry polymerization method is preferable since it enables the production of an ethylene-based resin with a regular particle shape. The solvent used in the slurry polymerization method may be any organic solvent that is generally used, for example, benzene, toluene, xylene, pentane, hexane, heptane, etc., and liquefied gases such as isobutane and propane, and olefins such as 1-butene and 1-hexene can also be used as the solvent.

[0023] The production catalyst used to produce the ethylene-based resin (iii) may be any catalyst capable of producing the ethylene-based resin. For example, in the case of multi-stage polymerization, a metallocene catalyst obtained from at least a transition metal compound (A-1), an organically modified clay modified with an aliphatic salt (B), and an organoaluminum compound (C) may be used. For example, in the case of a co-supported catalyst method, a metallocene catalyst obtained from at least a transition metal compound (A-1), a transition metal compound (A-2), an organically modified clay modified with an aliphatic salt (B), and an organoaluminum compound (C) may be used.

[0024] Examples of the transition metal compound (A-1) include transition metal compounds having a (substituted) cyclopentadienyl group and a (substituted) fluorenyl group, transition metal compounds having a (substituted) cyclopentadienyl group and a (substituted) indenyl group, transition metal compounds having a (substituted) indenyl group and a (substituted) fluorenyl group, and the like. In this case, examples of the transition metal include zirconium and hafnium, and among these, zirconium compounds having a (substituted) cyclopentadienyl group and an amino group-substituted fluorenyl group and hafnium compounds having a (substituted) cyclopentadienyl group and an amino group-substituted fluorenyl group are preferred, as they enable efficient production of ethylene-based resins suitable for injection molded articles.

[0025] More specifically, for example, diphenylmethylene(1-indenyl)(9-fluorenyl)zirconium dichloride, diphenylmethylene(1-indenyl)(2,7-di-t-butyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(4-phenyl-1-indenyl)(2,7-di-t-butyl-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2-(dimethylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2-(dimethylamino)-9-fluorenyl)zirconium dichloride, )(2-(diethylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2-(dibenzylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2,7-bis(dimethylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2,7-bis(diethylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2,7-bis (dibenzylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(4-(dimethylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(4-(diethylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(4-(dibenzylamino)-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dimethylamino)-9-fluorenyl)zirconium dichloride diphenylmethylene(cyclopentadienyl)(2-(diethylamino)-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(diisopropylamino)-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dibenzylamino)-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(diethylamino)-7-ethyl-9-fluorenyl)zirconium dichloride,Diphenylmethylene(cyclopentadienyl)(2-(diisopropylamino)-7-ethyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dibenzylamino)-7-ethyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dimethylamino)-7-n-propyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(diethylamino)-7-n-propyl-9-fluorenyl)zirconium dichloride diphenylmethylene(cyclopentadienyl)(2-(diisopropylamino)-7-n-propyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dibenzylamino)-7-n-propyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dimethylamino)-7-isopropyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(diphenylmethylene)(cyclopentadienyl)(2-(diphenylmethylene)(cyclopentadienyl) diphenylmethylene(cyclopentadienyl)(2-(diisopropylamino)-7-isopropyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dibenzylamino)-7-isopropyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dimethylamino)-7-n-butyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dimethylamino)-7-n-butyl-9-fluorenyl)zirconium dichloride Examples of zirconium compounds include diphenylmethylene(cyclopentadienyl)(2-(diisopropylamino)-7-t-butyl-9-fluorenyl)zirconium dichloride and diphenylmethylene(cyclopentadienyl)(2-(dibenzylamino)-7-t-butyl-9-fluorenyl)zirconium dichloride; zirconium compounds in which the dichloro form of these compounds is replaced with a dimethyl form, a diethyl form, a dihydro form, a diphenyl form or a dibenzyl form; and hafnium compounds in which the zirconium of these compounds is replaced with hafnium.

[0026] Examples of the transition metal compound (A-2) include a transition metal compound having a (substituted) cyclopentadienyl group and a (substituted) fluorenyl group, a transition metal compound having a (substituted) cyclopentadienyl group and a (substituted) indenyl group, and a transition metal compound having a (substituted) indenyl group and a (substituted) indenyl group.

[0027] More specifically, dimethylsilanediylbis(cyclopentadienyl)zirconium dichloride, diethylsilanediylbis(cyclopentadienyl)zirconium dichloride, dicyclohexylsilanediylbis(cyclopentadienyl)zirconium dichloride, diphenylsilanediylbis(cyclopentadienyl)zirconium dichloride, dimethylsilanediylbis(methylcyclopentadienyl)zirconium dichloride, diethylsilanediylbis(methylcyclopentadienyl)zirconium dichloride, dicyclohexylsilanediylbis(cyclopentadienyl)zirconium dichloride, Silanediylbis(methylcyclopentadienyl)zirconium dichloride, diphenylsilanediylbis(methylcyclopentadienyl)zirconium dichloride, dimethylsilanediylbis(2,4-dimethylcyclopentadienyl)zirconium dichloride, diethylsilanediylbis(2,4-dimethylcyclopentadienyl)zirconium dichloride, dicyclohexylsilanediylbis(2,4-dimethylcyclopentadienyl)zirconium dichloride, diphenylsilanediylbis(2,4-dimethylcyclopentadienyl)zirconium dichloride silanediyl[(cyclopentadienyl)(indenyl)]zirconium dichloride, dimethylsilanediyl[(cyclopentadienyl)(indenyl)]zirconium dichloride, diethylsilanediyl[(cyclopentadienyl)(indenyl)]zirconium dichloride, dicyclohexylsilanediyl[(cyclopentadienyl)(indenyl)]zirconium dichloride, diphenylsilanediyl[(cyclopentadienyl)(indenyl)]zirconium dichloride, dimethylsilanediyl[(cyclopentadienyl)(4,7-dimethylindenyl)]zirconium dichloride silanediyl[(cyclopentadienyl)(4,7-dimethylindenyl)]zirconium dichloride, dicyclohexylsilanediyl[(cyclopentadienyl)(4,7-dimethylindenyl)]zirconium dichloride, diphenylsilanediyl[(cyclopentadienyl)(4,7-dimethylindenyl)]zirconium dichloride, dimethylsilanediyl[(cyclopentadienyl)(2,4,7-trimethylindenyl)]zirconium dichloride, diethylsilanediyl[(cyclopentadienyl)(2,4,7-trimethylindenyl)]zirconium dichloride, dicyclohexylsilanediyl[(cyclopentadienyl)(2,4,7-trimethylindenyl)]zirconium dichloride, diphenylsilanediyl[(cyclopentadienyl)(2,4,7-trimethylindenyl)]zirconium dichloride, bis(indenyl)zirconium dichloride, isopropylidenebis(indenyl)zirconium dichloride, (methyl)(phenyl)methylenebis(indenyl)zirconium dichloride, diphenyl Phenylmethylene bis(indenyl)zirconium dichloride, ethylene bis(indenyl)zirconium dichloride, isopropylidene bis(2-methylindenyl)zirconium dichloride, (methyl)(phenyl)methylene bis(2-methylindenyl)zirconium dichloride, diphenylmethylene bis(2-methylindenyl)zirconium dichloride, ethylene bis(2-methylindenyl)zirconium dichloride, isopropylidene bis(tetrahydroindenyl)zirconium dichloride , (methyl)(phenyl)methylenebis(tetrahydroindenyl)zirconium dichloride, diphenylmethylenebis(tetrahydroindenyl)zirconium dichloride, ethylenebis(tetrahydroindenyl)zirconium dichloride, isopropylidene(cyclopentadienyl)(fluorenyl)zirconium dichloride, (methyl)(phenyl)methylene(cyclopentadienyl)(fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(fluorenyl)zirconium dichloride dichloride, ethylene(cyclopentadienyl)(fluorenyl)zirconium dichloride, isopropylidene(cyclopentadienyl)(2,7-di-t-butyl-fluorenyl)zirconium dichloride, (methyl)(phenyl)methylene(cyclopentadienyl)(2,7-di-t-butyl-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2,7-di-t-butyl-fluorenyl)zirconium dichloride, ethylene(cyclopentadienyl)(2,7-di-t-butyl-fluorenyl)zirconium dichloride; zirconium compounds in which the dichloro form of these compounds is replaced with a dimethyl form, a diethyl form, a dihydro form, a diphenyl form, or a dibenzyl form; and hafnium compounds in which the zirconium of these compounds is replaced with hafnium.

[0028] Examples of the organically modified clay (B) modified with an aliphatic salt include N,N-dimethyl-behenylamine hydrochloride, N-methyl-N-ethyl-behenylamine hydrochloride, N-methyl-Nn-propyl-behenylamine hydrochloride, N,N-dioleyl-methylamine hydrochloride, N,N-dimethyl-behenylamine hydrofluoride, N-methyl-N-ethyl-behenylamine hydrofluoride, N-methyl-Nn-propyl-behenylamine hydrofluoride, N,N-dioleyl-methylamine hydrofluoride, N,N-dimethyl-behenyl ... behenylamine hydrobromide, N-methyl-N-ethyl-behenylamine hydrobromide, N-methyl-Nn-propyl-behenylamine hydrobromide, N,N-dioleyl-methylamine hydrobromide, N,N-dimethyl-behenylamine hydroiodide, N-methyl-N-ethyl-behenylamine hydroiodide, N-methyl-Nn-propyl-behenylamine hydroiodide, N,N-dioleyl-methylamine hydroiodide, N,N-dimethyl-behenylamine sulfate, N-methyl-N-ethyl-behenylamine sulfate aliphatic amine salts such as N-methyl-Nn-propyl-behenylamine sulfate and N,N-dioleyl-methylamine sulfate; P,P-dimethyl-behenylphosphine hydrochloride, P,P-diethyl-behenylphosphine hydrochloride, P,P-dipropyl-behenylphosphine hydrochloride, P,P-dimethyl-behenylphosphine hydrofluoride, P,P-diethyl-behenylphosphine hydrofluoride, P,P-dipropyl-behenylphosphine hydrofluoride, P,P-dimethyl-behenylphosphine hydrobromide, P,P- Examples of the clay modified with an aliphatic salt include aliphatic phosphonium salts such as diethyl-behenylphosphine hydrobromide, P,P-dipropyl-behenylphosphine hydrobromide, P,P-dimethyl-behenylphosphine hydroiodide, P,P-diethyl-behenylphosphine hydroiodide, P,P-dipropyl-behenylphosphine hydroiodide, P,P-dimethyl-behenylphosphine sulfate, P,P-diethyl-behenylphosphine sulfate, and P,P-dipropyl-behenylphosphine sulfate.

[0029] The clay compound constituting the organically modified clay (B) may be any compound as long as it belongs to the category of clay compounds. In general, the organically modified clay (B) is formed by stacking many layers called silicate layers, which are composed of a tetrahedral sheet of silica tetrahedrons connected in two dimensions and an octahedral sheet of alumina octahedrons or magnesia octahedrons connected in two dimensions in a 1:1 or 2:1 ratio. The Si in some of the silica tetrahedra is replaced by Al, the Al in the alumina octahedrons by Mg, and the Mg in the magnesia octahedrons by Li, etc., resulting in a lack of positive charges within the layers and the layers as a whole being negatively charged. In order to compensate for this negative charge, Na is introduced between the layers. + Or Ca 2+ As the clay compound, there are natural or synthetic products such as kaolinite, talc, smectite, vermiculite, mica, brittle mica, and malachite, and these can be used, among which smectite is preferred because of its ease of availability and ease of organic modification, and among smectites, hectorite or montmorillonite is even more preferred.

[0030] The organically modified clay (B) can be obtained by introducing the aliphatic salt between the layers of the clay compound to form an ion complex. When preparing the organically modified clay (B), it is preferable to select conditions of a clay compound concentration of 0.1 to 30% by weight and a treatment temperature of 0 to 150°C. The aliphatic salt may be prepared as a solid and dissolved in a solvent for use, or a solution of the aliphatic salt may be prepared by chemical reaction in a solvent and used as is. As for the reaction ratio of the clay compound and the aliphatic salt, it is preferable to use an equivalent or greater amount of aliphatic salt relative to the exchangeable cations of the clay compound. Examples of the treatment solvent that can be used include aliphatic hydrocarbons such as pentane, hexane, and heptane; aromatic hydrocarbons such as benzene and toluene; alcohols such as ethyl alcohol and methyl alcohol; ethers such as ethyl ether and n-butyl ether; halogenated hydrocarbons such as methylene chloride and chloroform; acetone; 1,4-dioxane; tetrahydrofuran; water, and the like. It is preferable to use alcohols or water alone or as one component of the solvent.

[0031] In addition, the particle size of the organically modified clay (B) constituting the production catalyst is not limited, and is preferably 1 to 100 μm, since it is excellent in efficiency during catalyst preparation and efficiency during ethylene-based resin production. There is also no limit to the method of adjusting the particle size, and large particles may be crushed to an appropriate particle size, small particles may be granulated to an appropriate particle size, or crushing and granulation may be combined. In addition, the particle size may be adjusted either on the clay before organic modification or on the organically modified clay after modification.

[0032] As the organoaluminum compound (C), any compound that belongs to the category called an organoaluminum compound can be used, and examples thereof include alkylaluminum such as trimethylaluminum, triethylaluminum, and triisobutylaluminum.

[0033] The proportions of the transition metal compounds (A-1) and (A-2) (hereinafter, the transition metal compounds (A-1) and (A-2) are collectively referred to as component (A)), the organically modified clay (B) (hereinafter, also referred to as component (B)), and the organoaluminum compound (C) (hereinafter, also referred to as component (C)) constituting the production catalyst are not subject to any restrictions as long as they can be used as a production catalyst. In particular, in order to provide a production catalyst capable of efficiently producing the ethylene-based resin (C), the molar ratio per metal atom of component (A) to component (C) is preferably in the range of component (A):component (C)=100:1 to 1:100,000, and more preferably in the range of 1:1 to 1:10,000. Furthermore, the weight ratio of component (A) to component (B) is preferably component (A):component (B)=10:1 to 1:10000, and more preferably in the range of 3:1 to 1:1000.

[0034] Regarding the preparation method of the production catalyst, any method may be used as long as it is possible to prepare a production catalyst containing the (A) component, the (B) component, and the (C) component, and for example, a method of mixing the (A), (B), and (C) components in a solvent inert to the respective components, or using the monomer to be polymerized as a solvent, can be mentioned. In addition, there is no restriction on the order in which these components are reacted, and there is no restriction on the temperature and time of this treatment. In addition, it is also possible to prepare a production catalyst using two or more kinds of each of the (A), (B), and (C) components.

[0035] The polymerization conditions such as polymerization temperature, polymerization time, polymerization pressure, and monomer concentration when producing the ethylene resin (iii) can be arbitrarily selected, and among them, it is preferable to carry out the polymerization at a polymerization temperature of 0 to 100°C, for a polymerization time of 10 seconds to 20 hours, and at a polymerization pressure of normal pressure to 100 MPa. It is also possible to adjust the molecular weight by using hydrogen or the like during the polymerization. The polymerization can be carried out by any method such as a batch method, a semi-continuous method, or a continuous method, and it is also possible to carry out the polymerization in two or more stages by changing the polymerization conditions. The polymer particles obtained after the polymerization is completed can be separated and recovered from the polymerization solvent by a conventionally known method, and dried to obtain the product.

[0036] The polyethylene (iv) constituting the injection molded article of the present invention has an MFR of 0.1 to 100 g / 10 min and a density of 930 to 980 kg / m 3 Examples of the polyethylene include those mentioned above, and among them, high density polyethylene is preferable. Examples of such polyethylene include (product name) Nipolon Hard (manufactured by Tosoh Corporation) and (product name) Hi-Zex (manufactured by Prime Polymer Co., Ltd.). Here, if the MFR is less than 0.1 g / 10 min, the melt viscosity is too high and injection molding becomes difficult. Also, if the density is 980 kg / m 3 If the MFR exceeds 100 g / 10 min or the density exceeds 930 g / m, the resulting injection molded article will have poor mechanical strength. 3 If it is less than this, the injection moldability and / or mechanical properties will be inferior.

[0037] The amount of the ethylene resin (c) contained in the polyethylene composition (e) constituting the injection-molded article of the present invention may be any amount as long as the injection-molded article exhibits excellent mechanical properties. In particular, since the balance between the mechanical properties and processability is excellent, the polyethylene composition (e) preferably contains 1 to 100 parts by weight of the ethylene resin (c) per 100 parts by weight of the polyethylene (d), and more preferably 5 to 50 parts by weight.

[0038] The polyethylene composition (e) constituting the injection molded article of the present invention may be prepared by any method, and may be prepared by, for example, a method in which 1 to 100 parts by weight of an ethylene-based resin (c) is mixed with 100 parts by weight of polyethylene (d), and further, if necessary, additives usually used in polyolefins, such as weather resistance stabilizers, heat resistance stabilizers, antistatic agents, antislip agents, antiblocking agents, antifogging agents, lubricants, pigments, nucleating agents, plasticizers, antioxidants, antioxidants, UV absorbers, neutralizing agents, surfactants, slip agents, inorganic fillers, and organic fillers, and then mixed and kneaded by a kneading machine or the like. The conditions for this step may be any as long as the polyethylene composition (e) can be obtained, and may include, for example, a method in which the ethylene-based resin (c) and polyethylene (d), and optionally other additives, are heated, melted, and kneaded at a temperature in the range of 140°C to 250°C for about 20 to 500 seconds using a single-screw or twin-screw melt kneader or the like, and further cut into pellets to be used as an injection molding material. In addition, inorganic fillers may be blended as long as they do not impede the required physical properties, but when weight reduction is a priority, it is preferable not to blend inorganic fillers.

[0039] The injection molded article of the present invention can be produced by injection molding the polyethylene composition (e) using, for example, an injection molding machine and a mold having a gate. A known injection molding machine can be used in this case. The polyethylene composition (e) injected from the nozzle of the injection molding machine usually passes through a sprue and a runner, and flows into a mold cavity via a gate, and fills the mold cavity. A runner and a gate are formed in the mold used for injection molding, and a mold cavity for forming the injection molded article is formed. The shape of the sprue is not limited, and may be, for example, a circle, a rectangle, a trapezoid, etc. The shape of the runner is also not limited, and may be, for example, a circle, a rectangle, a trapezoid, etc. The runner type is also not limited, and may be, for example, a cold runner or a hot runner. The gate type is also not limited, and may be, for example, a direct gate, a side gate, a submarine gate, etc. Furthermore, there is no restriction on the number of gates per mold cavity; for example, a mold having either a single-gate structure or a multi-gate structure may be used. Since this enables efficient production, the number of mold cavities (number of mold cavities) of the mold is preferably 1 to 20.

[0040] When the polyethylene composition (e) is used to produce an injection-molded article, it can be injection-molded after drying, and when the polyethylene composition (e) is used to produce an injection-molded article, it is preferable to dry the polyethylene composition (e) before injection molding since this can suppress the generation of foaming and bubbles during molding. The dryer used in this case is not particularly limited as long as it can sufficiently reduce the water content in the polyethylene composition (e), and generally a dehumidified air dryer or the like can be used, and the drying temperature in this case is preferably 40°C to 80°C since this enables efficient drying.

[0041] The injection molding method for producing the injection molded article of the present invention is not particularly limited, and molding conditions such as injection speed, injection pressure, screw rotation speed, and back pressure can be set according to the injection molding machine and the shape and quality of the molded article (molded product). As an example of molding conditions, the molding temperature, molding cycle, and mold temperature are described below.

[0042] When the polyethylene composition (e) is made into an injection molded article, the cylinder temperature of the injection molding machine is not particularly limited as long as the desired molded article quality and productivity are satisfied, and is generally from the melting point of the polyethylene composition (e) to 280°C, for example, preferably from 150°C to 260°C, and more preferably from 160°C to 240°C. The molding cycle is not particularly limited as long as the desired molded article quality and productivity are satisfied, and is appropriately set in consideration of the molding temperature, mold temperature, weight and shape of the molded article, the number of molded articles (number of cavities), and the like. A typical molding cycle can be, for example, from 20 seconds to 300 seconds, and is preferably from 30 seconds to 180 seconds, since it is particularly excellent in cooling efficiency of the molded article and can obtain molded articles excellent in shape, strength, and color. The mold temperature is not particularly limited as long as the desired molded article quality and productivity are satisfied, and is generally from 25°C to 80°C, and more preferably from 30°C to 70°C, since the viscosity of the molten polyethylene composition (e) is low, thin-wall moldability is excellent, and the molding cycle can be maintained.

[0043] The injection molded article of the present invention has particularly excellent impact resistance. Therefore, the Charpy impact strength of a test piece (based on JIS K7111) taken from the injection molded article, measured using, for example, a universal impact tester (manufactured by Toyo Seiki Seisakusho, ISO-PE-Z43) with a support distance of 62 mm and a pendulum load of 2 J, is 10 kJ / m 2 It is preferably higher than 20 kJ / m 2 More preferably, it is equal to or greater than this.

[0044] In particular, since the surface has high hardness and excellent abrasion resistance, the surface of the non-curved portion of the molded body is scratched with a pencil of hardness H according to the method described in JIS K5600-5-4, except that the load is 100 g, and the unevenness of the scratched surface is measured as surface roughness using a laser microscope (e.g., VK-X200 (product name), manufactured by KEYENCE), and the surface roughness is preferably 2 μm or less.

[0045] The injection molded article of the present invention can be used for products with various applications, such as toys and parts thereof, insect repellent containers, containers for desserts such as jellies and puddings, beverage containers for alcoholic beverages, food containers for microwave ovens, housings for flow meters and valves, filter cages, nuts, bolts, joints, bearings, films, bottles, gaskets, tubes, hoses, pipes, seals, packing, tanks, rollers, connectors, pumps, wafer carriers, caps, and stoppers. Effect of the Invention

[0046] The injection moldability and mechanical strength of the molded article can be improved, and it is expected that the molded article will be made thinner and have a longer life, and it is therefore expected to be applied to a variety of uses. EXAMPLES

[0047] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to these examples as long as the gist of the present invention is not exceeded.

[0048] Unless otherwise specified, the reagents used were either commercially available or synthesized according to known methods.

[0049] The organically modified clay was pulverized using a jet mill (product name: CO-JET SYSTEM α MARK III, manufactured by Seishin Enterprise Co., Ltd.), and the particle size after pulverization was measured using a Microtrack particle size distribution measuring device (product name: MT3000, manufactured by Nikkiso Co., Ltd.) using ethanol as a dispersant.

[0050] The preparation of the catalyst for production, the production of the ethylene resin, and the purification of the solvent were all carried out under an inert gas atmosphere. The hexane solution (20 wt%) of triisobutylaluminum manufactured by Toso Finechem Co., Ltd. was used.

[0051] Furthermore, various physical properties of the ethylene resin and polyethylene were measured by the methods shown below.

[0052] ~Measurement of intrinsic viscosity ([η])~ The measurements were performed using an Ubbelohde viscometer, decahydronaphthalene as a solvent, at 135° C., and an ethylene resin concentration of 0.005 wt %.

[0053] ~Measurement of Mw and Mn~ Measurements were performed using an ultra-high temperature GPC (SSC-7110, manufactured by Senshu Scientific Co., Ltd.) equipped with a column (TSKgel GMHHR-H(S)HT, manufactured by Tosoh Corporation) with 1-chloronaphthalene as the eluent at a column temperature of 210°C, a sample concentration of 0.5 mg / ml, and an injection volume of 0.2 ml. The molecular weight calibration curve was calibrated using a standard polystyrene sample, and Mw and Mn were converted to linear polyethylene.

[0054] ~MFR~ The melt flow rate was measured at a temperature of 190° C. under a load of 2.16 kg in accordance with JIS6922-2:1997.

[0055] ~HLMFR~ The melt flow rate was measured at a temperature of 190° C. and a load of 21.6 kg in accordance with JIS6922-2:1997.

[0056] ~Measurement of thermal melting of ethylene resin~ Using a DSC (manufactured by SII NanoTechnology, Inc., product name: DSC6220), the temperature was raised from 0°C to 230°C at a heating rate of 10°C / min (1st scan), and the crystal melting peak (Tm 1 ), heat of fusion (ΔH 1 ) measurements were carried out.

[0057] Furthermore, various physical properties of the injection molded articles were measured by the methods shown below.

[0058] ~Tensile properties~ A tensile test was performed using a tensile tester (manufactured by Orientec Co., Ltd., product name: RTE-1210) at room temperature of 23°C and a tensile speed of 50 mm / min, using a sample punched out into a JIS K6301 (No. 4) dumbbell shape from a 2 mm thick portion of the injection molded body. The slope of the stress when the strain amount was 0.95 to 1% was measured as the tensile modulus.

[0059] ~Charpy impact strength~ Using a universal impact tester (manufactured by Toyo Seiki Seisakusho, ISO-PE-Z43), the impact strength of test pieces (compliant with JIS K7111) taken from the injection molded bodies was measured with a support distance of 62 mm and a pendulum load of 2 J.

[0060] ~Appearance of molded product~ The appearance of the injection molded article was evaluated visually. In addition, the surface gloss of the non-curved part of the injection molded article was measured at 10 points at a measurement angle of 60 degrees using a gloss meter manufactured by NIPPON DENSHOKU, and the average value and standard deviation were calculated. ○: No poor flow (so-called flow marks) or significant unevenness, the average surface gloss is 70% or more, and the standard deviation is less than 5%. ×: When significant unevenness occurs due to poor flow or gel, etc., or the average value of the above surface gloss is less than 70%, or the standard deviation is 5% or more.

[0061] ~Chemical resistance evaluation~ A slice cut from an injection molded product was used as a sample, and measurements were performed using an ultra-high temperature GPC (Senshu Scientific, product name SSC-7110) equipped with a column (Tosoh Corporation, product name TSKgel GMHHR-H(S)HT) at a column temperature of 210°C, a sample concentration of 0.5 mg / ml, and an injection volume of 0.2 ml, using 1-chloronaphthalene as the eluent. The molecular weight calibration curve was calibrated using a standard polystyrene sample, and the proportion of components with a molecular weight of less than 10,000 converted to linear polyethylene was calculated as an area ratio. When the proportion of components with a molecular weight of less than 10,000 was 20% or less, it was determined that the amount of elution when contacting the liquid was small, and was marked as ○, and when it exceeded 20%, it was marked as ×.

[0062] ~Evaluation of surface hardness~ The surface of the molded article produced by injection molding was scratched with a pencil of hardness H according to the method described in JIS K5600-5-4, except that the load was 100 g, and the unevenness of the mark was measured as the surface roughness using a laser microscope (Keyence, product name: VK-X200). The surface roughness was marked as ◯ when it was 0.8 times or less that of polyethylene not containing an ethylene polymer, and marked as × when it was more than 0.8 times.

[0063] Preparation Example 1 (1) Preparation of organically modified clay 300 ml of industrial alcohol (manufactured by Japan Alcohol Sales Co., Ltd., (trade name) Ekinen F-3) and 300 ml of distilled water were placed in a 1-liter flask, 15.0 g of concentrated hydrochloric acid and 42.4 g (120 mmol) of dimethylbehenylamine (manufactured by Lion Specialty Chemicals, (trade name) Lipomin DM22D) were added, and the mixture was heated to 45°C to disperse 100 g of synthetic hectorite (manufactured by BYK Additives Limited, (trade name) Laponite RDS), and then the mixture was heated to 60°C and stirred for 1 hour while maintaining the temperature. After filtering the slurry, it was washed twice with 600 ml of hot water at 60°C and dried in a dryer at 85°C for 12 hours to obtain 125 g of organically modified clay. This organically modified clay was pulverized in a jet mill to a median diameter of 10 μm.

[0064] (2) Preparation of catalyst suspension for production After replacing the air in a 300 ml flask equipped with a thermometer and reflux condenser with nitrogen, 25.0 g of the organically modified clay obtained in (1) and 108 ml of hexane were added, followed by 0.628 g of diphenylmethylene(cyclopentadienyl)(2-diethylamino-9-fluorenyl)zirconium dichloride and 142 ml of a hexane solution of 20 wt% triisobutylaluminum, and the mixture was stirred at 60°C for 3 hours. After cooling to 45°C, the supernatant was removed and washed twice with 200 ml of hexane, and then 200 ml of hexane was added to obtain a suspension of a catalyst for production (solid weight content: 12.5 wt%).

[0065] Preparation Example 2 (1) Preparation of organically modified clay The same procedure as in Preparation Example 1 was followed.

[0066] (2) Preparation of catalyst suspension for production After replacing the air in a 300 ml flask equipped with a thermometer and a reflux condenser with nitrogen, 25.0 g of the organically modified clay obtained in (1) and 108 ml of hexane were added, followed by 0.669 g of diphenylmethylene(cyclopentadienyl)(2,7-di-t-butyl-9-fluorenyl)zirconium dichloride and 142 ml of a hexane solution of 20 wt% triisobutylaluminum, and the mixture was stirred at 60°C for 3 hours. After cooling to 45°C, the supernatant was removed and washed twice with 200 ml of hexane, and then 200 ml of hexane was added to obtain a suspension of a catalyst for production (solid weight content: 12.5 wt%).

[0067] Preparation Example 3 (1) Preparation of organically modified clay In a 1-liter flask, 300 ml of industrial alcohol (product name Ekinen F-3, manufactured by Japan Alcohol Sales Co., Ltd.) and 300 ml of distilled water were added, and 15.0 g of concentrated hydrochloric acid and dioleylmethylamine ((C 18 H 35 ) 2 (CH 3 )N, 63.7g (120mmol) of (trade name) Lipomin MO (manufactured by Lion Specialty Chemicals Co., Ltd.) was added and heated to 45℃, after which 100g of synthetic hectorite (trade name Laponite RD, manufactured by BYK) was dispersed, and the temperature was raised to 60℃ and stirred for 1 hour while maintaining the temperature. After filtering the slurry, it was washed twice with 600ml of water at 60℃ and dried in a dryer at 85℃ for 12 hours to obtain 130g of organically modified clay. This organically modified clay was pulverized in a jet mill to a median diameter of 15μm.

[0068] (2) Preparation of catalyst suspension for production After replacing the air in a 300 ml flask equipped with a thermometer and a reflux condenser with nitrogen, 25.0 g of the organically modified clay obtained in (1) and 108 ml of hexane were added, followed by the addition of 0.392 g (1 mmol) of bis(indenyl)zirconium dichloride and 142 ml of a 20 wt% hexane solution of triisobutylaluminum, and stirring for 3 hours at 60°C. After cooling to room temperature, the supernatant was removed and washed twice with 220 ml of hexane, followed by the addition of 220 ml of hexane to obtain a suspension of a catalyst for production (solid weight content: 12.0 wt%).

[0069] Manufacturing Example 1 As described below, a bimodal polyethylene ethylene-based resin (III-1) was produced by two-stage polymerization in which the polymerization of component (III-1) was successively carried out after the polymerization of component (III-1). The ethylene-based resin (III-1) had an HLMFR of 2.3 g / 10 min and an [η] of 6.5 dl / g.

[0070] Manufacturing of component (A-1) 6 liters of hexane, 5.5 ml of a hexane solution of 20 wt% triisobutylaluminum, and 2.50 g (equivalent to 310 mg of solid content) of the suspension of the production catalyst obtained in Preparation Example 1 were added to a 10-liter autoclave, and the temperature was raised to 60°C. Ethylene was continuously fed so that the ethylene partial pressure could be maintained at 0.80 MPa, and slurry polymerization was carried out for 1 hour. 100 g of ethylene was consumed during the polymerization in terms of polyethylene, and the [η] of component (A-1) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 22 dl / g.

[0071] Manufacture of component (B-1) and ethylene resin (C-1) After polymerizing component (a-1), ethylene was continuously fed so that the ethylene partial pressure was maintained at 0.50MPa at 60°C, and hydrogen was added so that the hydrogen concentration in the gas phase of the autoclave was 4500ppm, and slurry polymerization was carried out for 9 hours to polymerize component (b-1), thereby producing ethylene-based resin (c-1), which is an ethylene homopolymer. During the polymerization, 900g of ethylene was consumed in terms of polyethylene, and the [η] of component (b-1) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 2.0dl / g.

[0072] Manufacturing Example 2 As described below, a bimodal polyethylene ethylene resin (III-3) was produced by two-stage polymerization in which the polymerization of component (III-2) was successively carried out after the polymerization of component (III-2). The ethylene polymer (III-2) had an HLMFR of 3.1 g / 10 min and an [η] of 4.1 dl / g.

[0073] Manufacturing of component (A-2) In a 10-liter autoclave, 6 liters of hexane, 5.5 ml of a hexane solution of 20 wt% triisobutylaluminum, and 2.50 g (equivalent to 310 mg of solid content) of the suspension of the production catalyst obtained in Preparation Example 2 were added, and the temperature was raised to 70°C. Ethylene was continuously fed so that the ethylene partial pressure could be maintained at 0.80 MPa, and slurry polymerization was carried out for 1 hour. During the polymerization, 200 g of ethylene was consumed in terms of polyethylene, and the [η] of component (A-2) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 10 dl / g.

[0074] Manufacture of component (B-2) and ethylene resin (B-2) After polymerizing component (a-2), ethylene was continuously fed so that the ethylene partial pressure was maintained at 0.87MPa at 60°C, and hydrogen was added so that the hydrogen concentration in the gas phase of the autoclave was 4500ppm, and slurry polymerization was carried out for 4 hours to polymerize component (b-2), thereby producing ethylene-based resin (c-2), which is an ethylene homopolymer. During the polymerization, 800g of ethylene was consumed in terms of polyethylene, and the [η] of component (b-2) calculated in relation to the hydrogen concentration in the system during the polymerization reaction was 2.0dl / g.

[0075] Production Example 3 As described below, a bimodal polyethylene ethylene resin (III-3) was produced by two-stage polymerization in which the polymerization of component (III-3) was successively carried out after the polymerization of component (III-3). The ethylene resin (III-3) had an HLMFR of 7.2 g / 10 min and an [η] of 3.2 dl / g.

[0076] Manufacturing of component (A-3) In a 10-liter autoclave, 6 liters of hexane, 5.5 ml of a hexane solution of 20 wt% triisobutylaluminum, and 2.50 g (equivalent to 310 mg of solid content) of the suspension of the production catalyst obtained in Preparation Example 2 were added, and the temperature was raised to 70°C. Ethylene was continuously fed so that the ethylene partial pressure could be maintained at 0.80 MPa, and slurry polymerization was carried out for 0.5 hours. During the polymerization, 100 g of ethylene was consumed in terms of polyethylene, and the [η] of component (A-3) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 10 dl / g.

[0077] Manufacture of component (B-3) and ethylene resin (B-3) After polymerizing component (a-3), ethylene was continuously fed so that the ethylene partial pressure was maintained at 0.87MPa at 60°C, and hydrogen was added so that the hydrogen concentration in the gas phase of the autoclave was 4500ppm, and slurry polymerization was carried out for 4.5 hours to polymerize component (b-3), thereby producing ethylene-based resin (c-3), which is an ethylene homopolymer. During the polymerization, 900g of ethylene was consumed in terms of polyethylene, and the [η] of component (b-3) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 2.0dl / g.

[0078] Production Example 4 As described below, a bimodal polyethylene ethylene resin (III-4) was produced by two-stage polymerization in which the polymerization of component (III-4) was successively carried out after the polymerization of component (III-4). The ethylene resin (III-4) had an HLMFR of 0.23 g / 10 min and an [η] of 6.6 dl / g.

[0079] Manufacturing of component (A-4) In a 10-liter autoclave, 6 liters of hexane, 5.5 ml of a hexane solution of 20 wt% triisobutylaluminum, and 2.50 g (equivalent to 310 mg of solid content) of the suspension of the production catalyst obtained in Preparation Example 2 were added, and the temperature was raised to 70°C. Ethylene was continuously fed so that the ethylene partial pressure could be maintained at 0.80 MPa, and slurry polymerization was carried out for 2.5 hours. During the polymerization, 500 g of ethylene was consumed in terms of polyethylene, and the [η] of component (A-4) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 10 dl / g.

[0080] Manufacture of component (B-4) and ethylene resin (B-4) After polymerization of component (a-4), ethylene was continuously fed so that the ethylene partial pressure was maintained at 0.87MPa at 60°C, and hydrogen was added so that the hydrogen concentration in the gas phase of the autoclave was 4500ppm, and slurry polymerization was carried out for 2.5 hours to polymerize component (b-4), thereby producing ethylene-based resin (c-4), which is an ethylene homopolymer. During the polymerization, 500g of ethylene was consumed in terms of polyethylene, and the [η] of component (b-4) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 2.0dl / g.

[0081] [Table 1]

[0082] Example 1 200 g of the ethylene resin (H-1) obtained in Production Example 1, polyethylene (manufactured by Tosoh Corporation, (product name) Nipolon Hard 4010 (MFR = 5.4 g / 10 min, density = 964 kg / m 3 800 g of NH4010 (hereinafter sometimes referred to as NH4010), 2 g of an antioxidant (BASF, (trade name) Irganox B225), and 1 g of calcium stearate (NOF Calcium Stearate) were dry-blended, and then melt-kneaded at 220°C, a screw rotation speed of 30 rpm, and a discharge rate of 0.8 kg / h using a twin-screw extruder (Toyo Seiki Seisakusho, (trade name) Labo Plastomill Parallel Twin-screw Extruder 2D25S) to obtain composition (E-1). The MFR of composition (E-1) was 0.11 g / 10 min.

[0083] The obtained composition (E-1) was dried at 60°C for 12 hours, and then, using an injection molding machine (manufactured by Niigata Machine Techno, product name MD100X i2.7) set at a cylinder temperature of 200°C and a mold temperature of 40°C, an injection molding cycle of 65 seconds was performed at an injection speed calculated according to formula (3) described in JIS K7152-1 in the range of 100±20 mm / s to produce gaskets with thicknesses of 2 mm and 4 mm as injection molded articles.

[0084] The obtained injection molded article had an excellent appearance, and test pieces were taken from the molded article and subjected to various tests, the results of which are shown in Table 2. The tensile modulus and Charpy impact strength were high, and the chemical resistance and surface hardness were excellent.

[0085] Example 2 A gasket was obtained as an injection-molded article in the same manner as in Example 1, except that 100 g of the ethylene-based resin (III-1) obtained in Production Example 1 was used as the ethylene-based resin, and 900 g of NH4010 was used as the polyethylene to form a composition (III-2).

[0086] The injection molded articles obtained were evaluated and the results are shown in Table 2.

[0087] Example 3 An injection-molded article was obtained in the same manner as in Example 1, except that 300 g of the ethylene-based resin (III-1) obtained in Production Example 1 was used as the ethylene-based resin, and 700 g of NH4010 was used as the polyethylene to prepare a composition (III-3).

[0088] The injection molded articles obtained were evaluated and the results are shown in Table 2.

[0089] Example 4 The polyethylene used was Nipolon Hard 5110 (trade name, MFR = 0.9 g / 10 min, density = 961 kg / m) manufactured by Tosoh Corporation. 3 An injection-molded article was obtained in the same manner as in Example 1, except that a composition (E-4) was prepared using NH5110 (hereinafter sometimes referred to as NH5110).

[0090] The injection molded articles obtained were evaluated and the results are shown in Table 2.

[0091] Example 5 An injection-molded article was obtained in the same manner as in Example 1, except that the ethylene-based resin (III-2) obtained in Production Example 2 was used as the ethylene-based resin to form a composition (III-5).

[0092] The injection molded articles obtained were evaluated and the results are shown in Table 2.

[0093] Example 6 An injection-molded article was obtained in the same manner as in Example 1, except that the ethylene-based resin (III-3) obtained in Production Example 3 was used as the ethylene-based resin to form a composition (III-6).

[0094] The injection molded articles obtained were evaluated and the results are shown in Table 2.

[0095] Example 7 An injection-molded article was obtained in the same manner as in Example 1, except that the ethylene-based resin (III-4) obtained in Production Example 4 was used as the ethylene-based resin to form a composition (III-7).

[0096] The injection molded articles obtained were evaluated and the results are shown in Table 2.

[0097] Example 8 An injection-molded article was obtained in the same manner as in Example 1, except that 100 g of the ethylene-based resin (III-4) obtained in Production Example 5 was used as the ethylene-based resin and 900 g of NH4010 was used as the polyethylene (III-8).

[0098] The injection molded articles obtained were evaluated and the results are shown in Table 2.

[0099] [Table 2]

[0100] Comparative Example 1 A composition (E-8) and an injection molded body were prepared in the same manner as in Example 1, except that 1000 g of polyethylene (NH4010), 2 g of an antioxidant (manufactured by BASF, (trade name) Irganox B225), and 1 g of calcium stearate (manufactured by NOF Corp., Calcium Stearate) were used.

[0101] The results of evaluation of the obtained injection molded articles are shown in Table 3.

[0102] Comparative Example 2 A composition (E-9) was prepared in the same manner as in Example 1 using 40 g of ultra-high molecular weight polyethylene (Mitsui Chemicals, Inc., product name Million 030S) and 960 g of polyethylene (NH4010), and injection molding was performed. However, the standard deviation of the surface gloss was large, and an injection molded article with good appearance could not be obtained. The evaluation results of the obtained molded article are shown in Table 3, and the improvement in the tensile modulus and Charpy impact strength was small compared to the case where only polyethylene was used.

[0103] Comparative Example 3 200 g of the ethylene resin (Ha-1) obtained in Production Example 1 and polyethylene (manufactured by Tosoh Corporation, (trade name) Petrothene 176 (MFR = 1.0 g / 10 min, density = 924 kg / m 3 A composition (E-10) was prepared in the same manner as in Example 1 using 800 g of a cellulose acetate copolymer (hereinafter sometimes referred to as P176), 2 g of an antioxidant (manufactured by BASF, (trade name) Irganox B225), and 1 g of calcium stearate (calcium stearate manufactured by NOF Corp.), and injection molding was performed, but an injection molded article with good appearance could not be obtained.

[0104] Comparative Example 4 200 g of the ethylene resin (H-1) obtained in Production Example 1 and polyethylene (manufactured by Tosoh Corporation, (product name) Nipolon Hard 8D01A (MFR = 0.05 g / 10 min, density = 957 kg / m 3 A composition (E-11) was prepared in the same manner as in Example 1, except that 800 g of an antioxidant (manufactured by BASF, (trade name) Irganox B225) and 2 g of calcium stearate (calcium stearate manufactured by NOF Corp.) were used, and injection molding was attempted, but a molded product could not be obtained.

[0105] [Table 3] [Industrial Applicability]

[0106] The injection molded article of the present invention can improve the injection moldability and mechanical strength of the molded article, and is expected to reduce the cost of the molded article, reduce its thickness, and extend its life.

Claims

1. (1) An ethylene-based resin having a melt flow rate (HLMFR) of 0.01 to 100 g / 10 min at a temperature of 190° C. and a load of 21.6 kg in accordance with JIS K6922-2:1997 and a bimodal elution curve measured by gel permeation chromatography; and a melt flow rate (MFR) of 0.1 to 100 g / 10 min at a temperature of 190° C. and a load of 2.16 kg in accordance with JIS K6922-2:1997 and a density of 930 to 980 kg / m as measured according to JIS K6922-1 (1997). 3 1. An injection-molded article, comprising a polyethylene composition comprising:

2. 2. The injection molded article according to claim 1, wherein the ethylene-based resin satisfies the following characteristic (2): (2) The elution curve measured by gel permeation chromatography has two peaks, and when the elution curve is expressed as a differential molecular weight distribution (x-axis: Log [M], y-axis: differential distribution value) and the peak is divided into two normal distributions according to the following formula (i), the following (2-1) to (2-3) are satisfied: f(x)=a×(1 / (2π(σ 2 )) (1/2) ) exp(-((x-μ) 2 ) / (2(s 2 ))) formula (i) (Here, a is the peak intensity, σ is the standard deviation, x is the variable, and μ is the average.) (2-1): The weight average molecular weight, calculated as linear polyethylene, based on the peak on the high molecular weight side is 900,000 to 5,000,000, and the molecular weight distribution, expressed as weight average molecular weight / number average molecular weight, is 2.0 to 5.

0. (2-2): The weight average molecular weight, calculated based on the peak on the low molecular weight side, is 10,000 to 500,000 in terms of linear polyethylene, and the molecular weight distribution is 2.0 to 5.

0. (2-3): The weight ratio of the high molecular weight peak to the weight ratio of the low molecular weight peak is greater than 5 / 95 and smaller than 80 / 20.

3. 3. The injection molded article according to claim 1, wherein the ethylene-based resin also satisfies the following characteristic (3): (3) The molecular weight distribution, calculated as standard polyethylene, measured by gel permeation chromatography is 4.0 or more and less than 50.

4. 3. The injection molded article according to claim 1, wherein the ethylene-based resin also satisfies the following characteristic (4): (4): The crystal melting peak (Tm) in the first scan measured using a differential scanning calorimeter by heating from 0° C. to 230° C. at a heating rate of 10° C. / min (1st scan) is single-peaked.

5. Using a test piece taken from the molded product, the Charpy impact strength measured at 23°C in accordance with JIS K7111 was 10 kJ / m 2 3. The injection molded article according to claim 1, wherein the viscosity is higher than 1000 ppm.

6. 3. The injection molded article according to claim 1, wherein the ethylene-based resin is an ethylene homopolymer.

Citation Information

Patent Citations

  • JP1973068853A

  • Thermal transfer type sheet

    JP1989005888A

  • Modifier for polyethylene resin, manufacturing method of polyethylene resin composition using the same and manufacturing method of molded body

    JP2017179304A

  • Ultra high molecular weight polyethylene

    JP2021172716A

  • polyethylene resin composition

    JP4173444B2